Gamification with Active Methodologies in Mathematics Learning in Secondary Education. - Moral-Sánchez, Silvia Natividad; Sánchez-Compaña, María Teresa (Pixel, 2024)
The continuous changes that society has undergone in recent years must be reflected in the classroom, which is a challenge for the educational system nowadays. Students who have been born and who are growing up in a digital age, they are digital native, they cannot adapt to traditional methodologies as usual and they demand a methodological shift more current. Active methodologies help this change, but if used one of these active methodologies in isolation, it may not be possible to take advantage of all the strengths that they offer. This proposal aims to make explicit the advantages of combining some of these active methodologies to form a mixed methodology that can cause a change in the educational paradigm in the subject of mathematics in Secondary Education. For this, we will explain how to embed methodologies such as cooperative learning, mobile learning or flipped learning within gamification strategies. Some results are offered through the observational and experiential method. This will help the student to be the protagonist by building autonomous, meaningful and more lasting learning, in addition to promoting motivation, acquisition of some skills and teamwork.
Keywords: Enseñanza - Innovaciones; Matemáticas - Estudio y enseñanza - Métodos activos; Gamificación; Educación matemática